Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.24071/jpsc.003018
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTIVENESS OF SOUTH SUMATRA COFFEE (Coffea arabica L.) EXTRACT CREAM IN BURN WOUND RECOVERY OF MALE WHITE MICE (Mus musculus)

Abstract: The effectiveness of South Sumatra coffee extract cream in burn wound recovery of white male mice had been analyzed. This research aims to ensure which one between immature and mature coffee bean that was better to recover burn wounds of male white mice after 14-day testing. The prepared concentrations for both coffee beans were 0.1%, 0.2%, and 0.3%. We then figured out that ethanol contained by young and old coffee beans had a recovery effect on burn wounds of male white mice (Mus musculus). Findings indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…A previous similar study revealed that coffee extract had an impact on healing burns in male rats. 28 The limitation of this study is that the observation of the burn healing process is limited at the end of the proliferative phase (14 th day) so the wound that is formed has not healed completely. In addition, Robusta coffee extract is only made in the form of gel preparation.…”
Section: Discussionmentioning
confidence: 96%
“…A previous similar study revealed that coffee extract had an impact on healing burns in male rats. 28 The limitation of this study is that the observation of the burn healing process is limited at the end of the proliferative phase (14 th day) so the wound that is formed has not healed completely. In addition, Robusta coffee extract is only made in the form of gel preparation.…”
Section: Discussionmentioning
confidence: 96%